The role of the audit committee to support the quality of financial reporting some lessons from Sox Act - Abdulhussein, Azher Subhi (Technium Social Sciences Journal, 2022)
The present study aims to demonstrate the effectiveness of the internal control system in large economic units as a result of the volume of business they practice. In light of the size of activity practiced by the General Company for the Distribution of Central Electricity through the distribution of electrical energy to six Iraqi provinces, there must be an important role for internal control in monitoring this activity. Hence, the present study focuses on evaluating the effectiveness of internal control in the company and its branches in light of the ethical code for senior officials contained in the Sarbanes- Oxley Act in addition to some other requirements that were dealt with by the law. The analysis of the data is based on some requirements in the law In addition to a questionnaire prepared for this purpose to measure the application of the code of ethical conduct for senior officials and to demonstrate the effectiveness of an efficient internal control system. 85 questionnaire forms were distributed to workers in the control, internal auditing, and accounting departments of the company and its branches. 74 forms were suitable for analysis. The present study concludes that there are indications that the internal control system is not independent in the provinces electricity distribution companies and the subsidiary companies. It is mentioned in the organizational structure of the company that the control and auditing department is subordinate to the director of the company and his/her assistants, and that it is not directly related to the official of the control and auditing department at the company’s headquarters, which may cause conflict in Interests and lack of coordination in control procedures.